Risk factors and correlation of secondary adjacent vertebral compression fracture in percutaneous kyphoplasty. (December 2016) - Yang, Shaofeng; Liu, Yanan; Yang, Huilin; Zou, Jun
Abstract: Background: To analyze risk factors and correlation of secondary adjacent vertebral compression fracture in percutaneous kyphoplasty. Materials and Methods: A total of 139 patients underwent PKP in our hospital for osteoporotic vertebral compression fracture between January 2013 and December 2014 and had completed follow-up data more than one year were selected randomly. Participants were divided into two groups in accordance with whether adjacent vertebral compression fracture occurred. The gender, age, body mass index, smoking history, bone mineral density, bone metabolic markers and affected vertebra number preoperative, balloon volume, cement volume, recovery rate of vertebral height, bone cement leakage intraoperative and anti-osteoporosis treatment postoperative, oswestry disability index and visual analog scale in the first three days after surgery were observed. Results: There was a statistically significant difference (P < 0.05) in bone mineral density value, balloon volume, cement volume, recovery rate of vertebral height and bone cement leakage between two groups. Conclusion: Patients with a lower bone mineral density value preoperative, larger balloon volume, cement volume, recovery rate of vertebral height and bone cement leakage intraoperative have an increased risk of adjacent vertebral compression fracture after percutaneous kyphoplasty. Highlights: Firstly investigates risk factors of adjacent vertebral compression fracture (AVCF) after percutaneous kyphoplasty (PKP). Patients with a higher recovery rate of vertebral height and bone cement leakage have an increased risk of AVCF. With a larger balloon and cement volume, AVCF risk increases sharply after PKP.